Awareness of Green Building Index (GBI) Implementation among Malaysian Contractors - Zarith Sufia, Azlan; Nur Syamimi, Zulkefli; Nurhaizan, Mohd Zainudin; Puteri Fadzline, Muhamad Tamyez (2015)
The Green Building Index (GBI) is Malaysia’s industry recognized green rating system for buildings which has been launched to promote sustainability in the built environment. The application of GBI has contributed varied perception and attitude among key players in the Malaysia construction industry mainly by the contractors. Two fields of studies, survey and interview have been conducted in this study to investigate the level of awareness, acceptance and application by the Malaysian contractors in adopting GBI system. Presently, the results indicate that majority of the respondents have lack of experienced in green building projects particularly in handling GBI’s rated project. This is due to lower level of understanding on the green building rating systems especially the GBI itself and concerned over high cost to their project. It is recommended that the GBI should be compulsory in rated all buildings in Malaysia and actions are needed to increase knowledge towards this system to all levels of contractors.